2013
DOI: 10.2753/pin1099-9922150402
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Permissiveness Toward Corruption?

Abstract: Understanding citizen corruption permissiveness can help clarify whether a general willingness to fight corruption exists in a society. Using 2005-2007 World Values Survey data from six Latin American countries, an index measuring corruption permissiveness was constructed. Results suggest that permissiveness varies by country and is associated with age, education, ethnicity, cultural values, and confidence in public organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…There is, however, a growing body of literature that suggests that citizens are not listening (Marquette 2007;Bauhr 2012;Persson et al 2013); there are few signs that global education and awareness efforts have led to citizens increasingly rejecting corruption or reporting it. Some believe trust in institutions plays a significant, and possibly greater, role in shaping citizen perceptions about and responses to corruption (Gorta and Forell 1995;Catterberg and Moreno 2005;Marquette 2007;de Sousa and Moriconi,2013;Lavena, 2013). Marquette (2007), for instance, suggests that the way citizens perceive formal institutions -including anticorruption institutions -may determine perceptions about and responses to corruption, as much as higher levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a growing body of literature that suggests that citizens are not listening (Marquette 2007;Bauhr 2012;Persson et al 2013); there are few signs that global education and awareness efforts have led to citizens increasingly rejecting corruption or reporting it. Some believe trust in institutions plays a significant, and possibly greater, role in shaping citizen perceptions about and responses to corruption (Gorta and Forell 1995;Catterberg and Moreno 2005;Marquette 2007;de Sousa and Moriconi,2013;Lavena, 2013). Marquette (2007), for instance, suggests that the way citizens perceive formal institutions -including anticorruption institutions -may determine perceptions about and responses to corruption, as much as higher levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that confidence in government can influence an individual's corruption perception (Catterberg & Moreno, 2005;Howard, 2002;Lavena, 2013;Melgar et al, 2010;Mishler & Roe, 1997;Zakaria, 2013b). In that respect, the present study argues that individuals with confidence in government will have a more positive view of the governing power, and so they would perceive corruption levels to be low.…”
Section: Experience and Confidencementioning
confidence: 96%
“…In addition, the authors found that unemployed individuals perceived corruption to be low. Lavena (2013) argues that wealth tends to influence an individual's acceptance and perception of corruption, where wealthy individuals "are more likely to believe that corruption is an acceptable way of preserving and advancing their position in society, because such behavior goes unpunished and social networks of corruption expand" (p. 351). The present study argues that a difference exists in corruption perception between self-employed and employed individuals in Croatia.…”
Section: Socioeconomic and Personal Attributesmentioning
confidence: 98%
See 1 more Smart Citation
“…Why do some individuals, social groups and/or regions perceive less corruption than others? The answers to these questions, according to Moreno (2002) and Lavena (2013), can help to explain why the willingness to fight corruption can be weaker and why the willingness to participate in the corrupt actions can be stronger in some societies compared to others. Low levels of perception of corruption in an environment where the level of corruption is high are very dangerous for any attempt to eradicate corruption efficiently.…”
Section: Study Background and Literature Reviewmentioning
confidence: 99%